Pengaruh Leverage, Risiko Bisnis, dan Profitabilitas Terhadap Nilai Perusahaan dengan Keputusan Investasi sebagai Variabel Moderasi (Studi pada Perusahaan Sub-Sektor Properti dan Real Estat yang Terdaftar Di Bursa Efek Indonesia Periode 2020–2024) - Ria Antonia Pattiasina; Atik Djayanti (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
The Effect of Leverage, Business Risk, and Profitability on Firm Value with Investment Decision as a Moderating Variable (Study on Property and Real Estate Sub-Sector Companies Listed on The Indonesia Stock Exchange (IDX) 2020-2024 Period) Ria Antonia Pattiasina ABSTRACT This study aims to analyze the effect of leverage, business risk, and profitability on firm value with investment decisions as a moderating variable in property and real estate sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research is motivated by the importance of firm value as an indicator of investor confidence in the company’s performance and future prospects, as well as the inconsistency of previous research findings regarding the factors affecting firm value. The independent variables in this study consist of leverage proxied by Debt to Equity Ratio (DER), business risk proxied by Degree of Operating Leverage (DOL), and profitability proxied by Return on Assets (ROA). The dependent variable, firm value, is proxied by Price to Book Value (PBV), while the moderating variable, investment decision, is proxied using the Investment Opportunity Set (IOS) through the Price Earnings Ratio (PER). This study employs a quantitative approach with a causal-comparative research design. The data used are secondary data obtained from annual reports and audited financial statements of property and real estate sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sampling technique used in this study is purposive sampling based on criteria relevant to the research objectives. Data analysis is conducted using panel data regression with Moderated Regression Analysis (MRA). The results of this study are expected to provide theoretical contributions to the development of financial management studies, particularly regarding the effects of leverage, business risk, profitability, and investment decisions on firm value. In addition, this study is also expected to serve as a consideration for investors, company management, and capital market regulators in making decisions related to enhancing firm value. Keywords: leverage, business risk, profitability, investment decision, firm value, panel data regression.Top of Form